2016
DOI: 10.1071/an15477
|View full text |Cite
|
Sign up to set email alerts
|

Proxies to adjust methane production rate of beef cattle when the quantity of feed consumed is unknown

Abstract: The aim of the present experiment was to evaluate the utility of carbon dioxide production rate (CPR; g CO2/day) and animal weight (WT) data as proxies for feed intake to adjust methane production rate (MPR; g CH4/day) in situations where dry-matter intake (DMI) is not known. This experiment measured individual-animal DMI, MPR and CPR in the feedlot, and then again on restricted quantities of grain and roughage diets in open-circuit respiration chambers. Of the 59 cattle tested in the feedlot, 41 had MPR and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 5 publications
5
14
1
1
Order By: Relevance
“…The correlation was noticeably high between CH 4 and CO 2 (R p = 0.83 and 0.86). Similar high relationships, R p = 0.78 on average (R p = 0.57 to 0.91), were estimated with yearling beef cattle [16,18,26], dairy cows [28] or with lambs [29], measured either in respiratory chambers or with GreenFeed systems. The two emission rates were also highly correlated with the heifer body weight, slightly more for CO 2 (R p = 0.77 and 0.85) than for CH 4 (R p = 0.68 and 0.70).…”
Section: Recorded Traitssupporting
confidence: 60%
See 4 more Smart Citations
“…The correlation was noticeably high between CH 4 and CO 2 (R p = 0.83 and 0.86). Similar high relationships, R p = 0.78 on average (R p = 0.57 to 0.91), were estimated with yearling beef cattle [16,18,26], dairy cows [28] or with lambs [29], measured either in respiratory chambers or with GreenFeed systems. The two emission rates were also highly correlated with the heifer body weight, slightly more for CO 2 (R p = 0.77 and 0.85) than for CH 4 (R p = 0.68 and 0.70).…”
Section: Recorded Traitssupporting
confidence: 60%
“…Methane yield (CH 4 /DMI) and the residual methane emission (r wi CH 4 ) were moderately correlated (R p = 0.44 and 0.54). Herd et al [18] found a closer relationship (R p = 0.89) between CH 4 /DMI and r i CH 4 with a limited number of animals.…”
Section: Calculated Growth and Methane Efficiency Traitsmentioning
confidence: 88%
See 3 more Smart Citations